Social Representations of Sustainable Tourism Development in Mass Tourism Destinations: The Case of Antalya, Turkey - Çevik Ünlü, Birsen; İçigen, Ebru (International Journal of Contemporary Economics and Administrative Sciences, 2025)
In the context of social representation theory, the aim of this study is to explore the social representations of sustainable tourism development in Antalya, a mass tourism destination, specifically focusing on hotel operators (hotel owners). In line with the research purpose, a qualitative research method was chosen. As a data collection technique, the free association method, which is considered an important technique, was used to uncover the constituent elements of the representation content. Interviews were conducted with 15 individuals who are hotel operators of four- or five-star establishments in Antalya. Five basic categories were identified: environmental, economic, cultural, social, and managerial. It is observed that the representations primarily revolve around environmental concerns, with recurring themes including recreational activities, employment, and urban planning. Furthermore, through multiple correspondence analysis, the proximity of participants to the social representations within their respective generation and education level was determined. Lastly, this study stands out as one of the few endeavors to ascertain the social representations of sustainable tourism development in mass tourism cities.